Histórias em quadrinhos (HQs) para o ensino de Biologia: uma abordagem para aprendizagem ativa sobre doenças cardiovasculares - SILVA, Erick José dos Santos (Universidade Federal do Pará, 2022)
The present research comprises a study of validation of educational product conceived in the form of a Methodological Strategy called Comics in Comics (HQs) for the teaching of Biology: an approach to active learning about cardiovascular diseases. This strategy is intended to be a guiding tool for Biology teachers who plan to use HQs in their classes, in order to collaborate with students' active learning. The research approach employed involved two stages, in which the first consisted of the development and construction of the methodological strategy aimed at teaching cardiovascular diseases through the construction of HQs and the second stage contemplates the validation research, which was carried out with teachers of Basic education biology. The criterion for choosing the subjects participating in the research (teachers) was that they were in continuing education at the master's level, aimed at teaching Biology. In this sense, 16 (sixteen) teachers regularly enrolled in two classes of Professional Master's in Biology Teaching, in a Federal Public University, participated in this research in the year 2020. For this validation, an online questionnaire was used during data collection. data, which took into consideration for the analysis two fundamental aspects: the technical aspects and the pedagogical aspects. From the data collection it was possible to tabulate, perform the analysis and verify the contributions of this strategy to the teaching of Biology, as well as identify aspects that need to be improved. In this sense, the data analysis indicated that the methodological strategy was well accepted by teachers participating in the research and that, in general, it is suitable for its application in basic education, as well as indicated aspects that can be improved, in order to contribute better use in schools.